Meninjau Soteriologi dan Kristologi Saksi Yehovah - Imeldawati, Tiur; Simamora, Elim (STT Injili Indonesia Medan, 2022)
In reality, Christianity has experienced a long history and has been faced with various false teachings or heresies throughout the history of the church. This is the case at the moment. One issue that remains hot to discuss is Christology and Soteriology. In this study the author tries to conduct a study of the teachings of the Jehovah's Witnesses related to these two topics, and through library research, it is hoped that the research formulation can be answered. The author takes part to make this contribution, by conducting a study of the challenges faced by systematic theology today, namely from the Jehovah's Witness school. By adhering to the truth of the Bible and the right approach in the science of commentary or hermeneutics, the author is sure to be able to deliver relevant presentations for readers who also take part in theological studies. Truth must be held fast and faithfully taught. The Bible is the source of absolute truth where its authority is firmly held in living the Christian life.Keywords: soteriology, Christology, jehovah’s witness, theology